A Scale to Measure Farmers’ Perception of Capacity Needs under NICRA (Indian Journal of Extension Education, 2025)
A study conducted in 2024 developed and standardized a summated-rating scale to measure farmers’ perceptions of capacity needs under the National Innovations in Climate Resilient Agriculture (NICRA) program. An initial pool of 155 statements was generated from literature and expert consultation, then screened by 100 judges (41 responses) and reduced to 80 items using a relevancy index threshold of >80. The 80 items were pilot tested with 32 farmers in a non-sampled area; item analysis followed Edwards’ top/ bottom 25 per cent t-test procedure, and 31 items with t > 2.145 were retained. The final instrument’s reliability was assessed using the split-half method with 40 respondents (odd–even split), yielding a coefficient of 0.955. Criterion validity was examined by correlating perception scores with operational landholding; the correlation was moderate (r = 0.531), supporting the scale’s validity. The resulting scale provides a consistent and interpretable measure of farmers’ capacity-need perceptions under NICRA and can inform targeting of training, advisory, and monitoring interventions. The tool is adaptable to other locations and projects with minor contextual changes.